The shared microbiome in mud crab (Scylla paramamosain) of Sanmen Bay, China: core gut microbiome - Jiang, Xiaosong; Niu, Mingming; Qin, Kangxiang; Hu, Yun; Li, Yuntao; Che, Chenxi; Wang, Chunlin; Mu, Changkao; Wang, Huan (Frontiers in Microbiology, 2023)
The mud crab, Scylla paramamosain, holds great commercial significance as a marine crustacean widely cultivated in the Indo-Pacific region. Understanding the core gut microbiota of aquatic animals is crucial for their overall health and growth, yet the core gut microbiota of mud crab remains poorly characterized. In this study, we investigated the gut microbial diversity of mud crabs from Sanmen Bay. Our results demonstrate that the gut microbial diversity of mud crab did not exhibit significant variation among the five sampling sites, although there were some differences in community richness.At the phylum level, we identified 35 representative phyla, with Firmicutes, Proteobacteria, Bacteroidota, and Campilobacterota as the dominant phyla. Among the 815 representative genera, we discovered 19 core genera, which accounted for 65.45% of the total sequences. These core genera were distributed across 6 phyla, and among them, Photobacterium exhibited the highest average relative abundance.Photobacterium has probiotic activity and may play a crucial role in enhancing the immune response of the host and maintaining the diversity of the gut microbiota. Moreover, we observed a positive correlation between the relative abundance of core genera and the stability of the gut microbial community. Furthermore, our findings revealed distinct differences in gut microbial composition and specific taxa between the sexes of mud crab. These differences subsequently influenced the functionality of the gut microbial community. Overall, our investigation sheds light on the core gut microbiota of mud crab, emphasizing the importance of core gut microbial communities in maintaining the health and growth of these commercially significant marine crustaceans.